Preferensi Wisatawan Perempuan terhadap Keputusan Membeli dan Menginap pada Hotel Ramah Lingkungan dan Berkelanjutan di Kabupaten Karangasem: Female Travelers' Preferences for Purchasing and Staying Decisions at Eco-Friendly and Sustainable Hotels in Karangasem Regency - Kusumarini, Indah; Diwyarthi, Ni Desak Made Santi; Citrawati, Luh Putu; Darmiati, Made; Wiartha, Nyoman Gede Mas (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The increasing number of tourists and awareness of environmentally friendly hotels has encouraged the birth of research that analyzes the preferences of female tourists towards the decision to buy and stay at environmentally friendly and sustainable hotels in Karangasem Regency. This study uses a descriptive research method with a quantitative approach to 100 female tourist respondents who stayed at environmentally friendly and sustainable hotels in Karangasem Regency. Data collection techniques using questionnaires, observations, interviews and documentation studies. Data analysis techniques using SPSS tools to test the validity and reliability of the data. The results of the Factor Analysis using the Kaiser Meyer-Olkin Measure of Sampling Adequacy to test the significance of the attributes of each factor. Based on the correlation coefficient values ??of the attributes and attribute levels of environmentally friendly and sustainable hotels in Karangasem Bali, it is known that female tourists tend to pay more attention to the group of attractive advertising attributes, the number of followers, and promotions by famous artists with the highest correlation coefficient of 0.786 when choosing a hotel. The second important attribute group is friendly service and speed and accuracy of service with a correlation coefficient of 0.684. The third important attribute group includes the completeness of hotel facilities and the presence of local communities with a correlation coefficient of 0.283. However, ease of hotel access, display of advertisements in mass media, and local cultural activities are considered less important with a correlation coefficient of -0.727. Female travelers' preferences in choosing a hotel are also influenced by recommendations from others such as friends, colleagues, and family. Female travelers' preferences for purchasing and staying at environmentally friendly and sustainable hotels in Karangasem Regency